Legislative regulating of the institution of witnesses - Лук'янчиков, Є.Д; Лук'янчиков, Б.Є (Київський національний університет імені Тараса Шевченка, ТОВ «Правова Єдність», 2015)
In the article it is exposed the establishing of the concept of witness in the criminal proceedings. It is made attention to the fact that the new Criminal Procedure Code of Ukraine gives them the rights of the participants in a criminal case. It is made attention to the fact that the witness is referred as a participant in a criminal case but this person isn’t mentioned in the independent chapter of the Criminal Procedure Code that contains the norms concerning the others participants in a criminal case. It is developed the reasons and the conditions to engage the witness for the investigative (search) actions. It is formulated the proposals about the altering this concept. Analysis of the CPC shows that the proceedings of the proceedings of the concepts involved other persons: the suspect or the accused, defense counsel, victims, witnesses, experts, specialists, and representatives, educators and others. The presence of these persons and adherence to the law and the rules of procedural steps are believed to be fully safeguard the rights and legitimate interests of stakeholders. But lawmakers believe this is not enough and defines investigative (search) action (search or inspection of housing or other property), participation in the proceedings which witnesses are required.

Проаналізовано розвиток інституту понятих у кримінальному провадженні. Акцентовано увагу, що новий КПК України наділяє його правами учасника кримінального провадження. Звернено увагу на те, що назвавши понятого учасником провадження, йому не приділено увагу у самостійному розділі КПК, який присвячено «іншим учасникам кримінального провадження». Висвітлено підстави та умови залучення понятих до проведення процесуальних дій. Обґрунтовано пропозиції щодо змін у даному інституті.
ЗАКОНОДАВЧЕ РЕГУЛЮВАННЯ ІНСТИТУТУ ПОНЯТИХ
Keywords: witness; investigator; investigative (search) actions; specialist; expert; понятий; слідчий; процесуальні дії; слідчі (розшукові) дії; незаінтересовані особи; спеціаліст